Adorno's gamble : harnessing German ideology - Immanen, Mikko, 1982- (Cornell University Press and Cornell University Library, 2025)
"The book reinterprets the thought of Theodor W. Adorno, the leading light of the Frankfurt School and one of the most influential leftist intellectuals of the twentieth century, by arguing that his worries over the frailty of reason and democracy were inspired by radical conservative thinkers of Weimar Germany"-- Provided by publisher.
Keywords: Adorno, Theodor W., -- 1903-1969.; Spengler, Oswald, -- 1880-1936 -- Influence.; Klages, Ludwig, -- 1872-1956 -- Influence.; Philosophy, German -- 20th century.; Frankfurt school of sociology.; Philosophie allemande -- 20e siècle.; École de Francfort (Sociologie); LITERARY CRITICISM / European / German.; Electronic books.